Representing Corruption and Arabic Terms in Online News: An SFL Transitivity Study - Hanifah Mu'izah; Frans Sayogie; Abdullah Abdullah (Indonesian Journal of EFL and Linguistics, 2026)
This study examines the portrayal of corruption and the use of Arabic terms in four online news articles published by Kompas.com and Detik.com in May–June 2017. The case involved a member of the House of Representatives from the PKS faction, Yudi Widiana Adia, who was suspected of using Arabic terms as code in communications related to bribery surrounding road construction projects in Maluku and North Maluku. Adopting a qualitative-descriptive approach grounded in Systemic Functional Linguistics (SFL), this study focuses on the transitivity system within the ideational metafunction to analyze how each media outlet linguistically constructs the same corruption incident. The findings indicate that Kompas tends to represent corruption through material processes that position the actors as the agents of the action, whereas Detik more frequently employs verbal processes that position the source as the primary speaker. This difference also influences how Arabic terms are represented in the context of corruption. These consistent linguistic patterns indicate a difference in editorial orientation between the two media outlets in their coverage of the same corruption case, although broader generalizations require a more extensive corpus analysis.